THE PRODUCTION OF SENSE IN THE HYPERTEX WAY - Ana Paula Domingos Baladeli (Travessias, 2010)
The information and communication technologies spread the spaces for communication and interaction in the same way that changes the use of language. In this context, because of non-linear and open nature the hypertext challenges the reader in the production of sense on web during the multiple connection between information pad and others texts. Besides that, intertextuality and the convergence between verbal, visual and sound languages differs reading in hypertext from reading press text.